Dampak Kebijakan Luar Negeri RRT di Amerika Latin terhadap Perekonomian Brazil - St. Husnul Khatimah; Agussalim Burhanuddin; Aswin Baharuddin (Department of International Relations, Hasanuddin University, 2021)
This study aims to provide an overview of the implementation of China's foreign policy in Latin America within the framework of peaceful development as a manifestation of China's identity and interests in the region. Furthermore, this study also aims to see the extent of the impact of China's policies in Latin America on the Brazilian economy. The type of research that the author uses is a qualitative method with data collection techniques in the form of literature review/library research. The data used is secondary data sourced from reports, journals, articles, books and other documents which are then analyzed qualitatively by descriptive-analytic method. The results of this study indicate that China's foreign policy towards Latin America based on peaceful development is oriented towards mutual development through increasing cooperation in various fields. The implementation of China's foreign policy in Latin America in this case is carried out in two forms: multilateral cooperation through inter-regional organizations, in particular the CELAC-China Forum as the main structure; and bilateral cooperation with each country in the region. In practice, the two forms of cooperation are carried out synergistically and simultaneously, and are open to the participation of countries outside the region. In the context of Brazil, China's foreign policy in Latin America has more or significant impact, though not comprehensively. By looking at the increase in Brazil's GDP and the PRC's global investment figures in the country during China's joining the CELAC-China Forum and the implementation of the China-Latin American and Caribbean Countries Cooperation Plan (2015-2019) since 2015, it can be said limitedly that China's development oriented economic policy has had a positive impact on the Brazilian economy. Penelitian ini bertujuan untuk memberikan gambaran mengenai bentuk implementasi kebijakan luar negeri RRT di Amerika Latin dalam kerangka peaceful development sebagai wujud identitas dan kepentingan RRT di kawasan tersebut. Lebih lanjut, penelitian ini juga bertujuan untuk melihat sejauh mana dampak kebijakan RRT di Amerika Latin terhadap perekonomian Brazil. Tipe penelitian yang penulis gunakan adalah metode kualitatif dengan teknik pengumpulan data berupa studi literatur/telaah pustaka. Data yang digunakan berupa data sekunder, bersumber dari laporan, jurnal, artikel, buku serta dokumen lain yang kemudian dianalisis secara kualitatif dengan metode deskriptif-analitik. Hasil penelitian ini menunjukkan bahwa kebijakan luar negeri RRT terhadap negara-negara di kawasan Amerika Latin berdasarkan peaceful development berorientasi pada pembangunan bersama melalui peningkatan kerja sama di berbagai bidang. Implementasi kebijakan luar negeri RRT di Amerika Latin dalam hal ini diterapkan melalui dua bentuk: kerja sama multilateral melalui organisasi inter-regional, khususnya Forum CELAC-Tiongkok sebagai struktur utama; dan kerja sama bilateral dengan masing-masing negara di kawasan. Pada praktiknya, kedua bentuk kerja sama tersebut dilakukan secara sinergis dan simultan, serta terbuka terhadap keikutsertaan negara-negara di luar kawasan. Dalam konteks Brazil, kebijakan luar negeri RRT di Amerika Latin kurang lebih memberikan dampak yang cukup signifikan, meskipun tidak menyeluruh. Dengan melihat pada kenaikan PDB Brazil dan angka investasi global RRT di negara tersebut sepanjang bergabungnya Tiongkok dalam CELAC-China Forum beserta implementasi China-Latin American and Caribbean Countries Cooperation Plan (2015-2019) sejak tahun 2015, maka dapat dikatakan secara terbatas bahwa kebijakan ekonomi berorientasi pembangunan bersama yang dijalankan RRT memiliki dampak positif terhadap perekonomian Brazil.